Impact of heart rate variability-based exercise prescription: self-guided by technology and trainer-guided exercise in sedentary adults - Casanova-Lizón, Antonio; Manresa-Rocamora, Agustín; Sarabia, José Manuel; Pastor, Diego; Javaloyes, Alejandro; Peña-González, Iván; Moya-Ramón, Manuel (Frontiers in Sports and Active Living, 2025)
IntroductionExercising at home is an accessible alternative to the gym, although it presents challenges such as low adherence, poor quality and difficulties in reaching set goals. Wearable technologies and the use of heart rate variability (HRV) make it possible to personalise workouts, optimise fitness and improve adherence. However, specific exercise recommendations based on these metrics are still lacking. This study evaluated the impact of HRV-based training using the Selftraining UMH app in an autonomous format versus a Personal Trainer-led approach.MethodsSeventy sedentary adults were divided into three groups: Autonomous (n = 18), Personal Trainer (n = 23), and Control (n = 29). After a two-week baseline HRV assessment, participants underwent an 11-week intervention, with pre- and post-tests on peak oxygen uptake, aerobic power, total test time, strength, and HRV.ResultsBoth intervention groups completed similar session numbers (23.3 vs. 24.5) and high-intensity workouts (13.7 vs. 14.6). Both groups improved significantly (p < 0.05) across all fitness metrics, except aerobic power in the Autonomous group. Effect sizes ranged from small to large (0.21–1.12 Autonomous; 0.23–1.63 Personal Trainer). Strength improvements were greater in the Personal Trainer group, and both outperformed the Control group (p < 0.05) on all variables except aerobic power in the Autonomous group.ConclusionsThe findings demonstrate that HRV-based training effectively enhances fitness in sedentary adults, with both delivery methods showing similar adherence and benefits. The Selftraining UMH app offers an accessible alternative for autonomous exercise, particularly in settings without professional supervision, promoting improved population health outcomes.